Comparative Study of the Nutritional Value, Phytochemicals, and Sensory Quality of Flakes Prepared Using Elicited and Non-Elicited Cowpea Sprout Flours - Setyaningrum Ariviani; Galih Poetri Nastiti; Nurul Hidayati Sholihin; Gusti Fauza; Siswanti Siswanti (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Germination without and with elicitation using 50 mM NaCl or 250 ppm Na-alginate generated cowpea sprout flours with the levels of protein, total phenolic compounds (TPC), total flavonoid compounds (TFC), radical scavenging activity (RSA), and ferric reducing antioxidant power (FRAP), as well as functional properties that significantly higher than that of cowpea seed flour. Most cereal flakes lack protein content and health-promoting compounds. This study aims to investigate the potential for developing NaCl-elicited, Na-alginate-elicited, and non-elicited cowpea sprout flours for flakes production through a comparative study on the nutritional value (proximate, dietary fibers), phytochemicals (TPC, RSA, FRAP), and sensory quality. Oat-based commercial flake was used as a comparator. The flakes formulated using elicited cowpea sprout flours exhibited significantly lower fat and carbohydrate contents and higher levels of protein, soluble, insoluble, and total dietary fibers than those prepared using non-elicited cowpea sprout flour. The cowpea-based flakes showed more elevated carbohydrate, total, soluble, and insoluble dietary fiber levels and significantly lower fat levels than oat-based commercial flakes. The flakes designed using Na-alginate-elicited cowpea sprout flour have the highest TPC, RSA, and FRAP values. Compared to the commercial ones, flakes prepared with elicited cowpea sprout flours produce better aroma, texture, and overall qualities. These results have significant implications for developing legume-based flakes with lower fat, higher levels of protein, dietary fibers, and phytochemicals, as well as good sensory quality.